Optimasi Dosis Koagulan Aluminium Sulfat Al2 (SO4)3 Pada Ipam PT Hanarida Tirta Birawa Sidoarjo - Nursinta Abadiyah; Yayok Suryo Purnomo (Jurnal Kendali Teknik dan Sains, 2024)
In drinking water treatment plants, there is a coagulation unit that requires coagulant substances. Coagulant dosage determination can be done using the jartest method. By carrying out a jar test, the correct dose will be known so that the coagulation process runs well, and the use of coagulants can be optimized. This research was carried out by analyzing jartest results from the company's internal laboratory for one week with two variations in jartest times in one day. The raw water used comes from shipping rivers with a company production capacity of 500 l/second. The dosage of Aluminum Sulphate coagulant used in the field is 165 mg/l, while the jastest results show that the optimum dosage is 140 mg/l. This research is expected to provide scientific information regarding determining coagulant dosage at IPAM PT Hanarida Tirta Birawa which makes it easier for installation operators.